Student errors in solving system of linear equations in two variables story problems based on Newman error analysis - Fatah, Zakiyah; Sukoriyanto, Sukoriyanto (Universitas Islam Negeri Sumatera Utara Medan, 2024)
The purpose of this study was to describe the types of errors and their causes made by eighth-grade students in solving system of linear equations in two variables (SLETV) problems and to propose solutions to overcome them using the NEA (Newman Error Analysis) procedure. The research method used was descriptive research with a qualitative approach. In this study, data collection involved tests and interviews. The test instrument included a written test with two story problems related to SLETV material in the form of essays. At the same time, interviews were conducted with teachers as a preliminary study and with selected students to determine the types of errors made in solving the given questions. The researcher selected three students as research subjects from all students in class VIII A who made various errors in the interview questions, with one student chosen additionally for their good communication skills. The results showed that the stage with the lowest error rate fell within the sufficient and good categories. Conversely, the answer-writing stage exhibited a high error rate, as all students fell into the less capable category